PENGUATAN KARAKTER RELIGIUS MELALUI PROGRAM PEMBINAAN KARAKTER PADA BADAN PUSAT KECERMELANGAN DIRI DI SEREMBAN, NEGERI SEMBILAN, MALAYSIA - Abdul Wahab; Andi Bunyamin; Junaedi; Naharuddin; Nur Aeni F (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This community service program aims to strengthen the religious character of participants through a structured mentoring and character development system carried out at the Badan Pusat Kecemerlangan Diri (BPKD) in Seremban, Negeri Sembilan, Malaysia. The main problems identified include the weak internalization of religious values among participants, low discipline in worship, limited ethical conduct in social interaction, and the absence of a practical module to support the systematic development of religious character. To address these challenges, this program was implemented through a participatory and continuous approach consisting of needs assessment, development of a contextual religious character module, capacity building for local facilitators, implementation of mentoring and habituation programs, and structured monitoring and evaluation. The results showed a significant increase in participants’ understanding and practice of religious behavior, especially in performing prayers on time, regular Qur’an recitation, respectful communication, self-discipline, and responsibility in daily life. The “21-Day Religious Habituation Program” proved effective in shaping consistent religious routines and supporting long-term behavioral change. In addition, the program succeeded in strengthening the competence of BPKD facilitators in facilitation, character observation, and use of evaluation instruments, enabling them to independently continue mentoring activities. This mentoring model contributed not only to improving participants’ religious character but also to ensuring the sustainability of character development activities within the institution. The model developed in this program has the potential to be replicated in other community-based Islamic character education initiatives in Malaysia and Southeast Asia.